Creating ties: a management of communication and of education in private teaching organizations - Arashiro, Leda Márcia (Comunicação & Educação, 2008)
The communication processes are in all the organizations. In the Institutions of Education, in particular, them they would have fluent and to be integrated, and the planning of the communication would have to be to complement to the proposal pedagogical, therefore an adequate planning of the processes of communication in educational environments reflects in one better organization of the activities, with consequent improvement of the exploitation of the students. However, in general, the private Institutions of Education tend to have hierarchical processes of communication, that they make the process doesn’t flow between departments, employees, teachers, students and their parents. The interaction between Communication and Education can create work proposals that propitiate a healthful processe of communication.One of these proposals is the organization of a school memorial as starting point for the formation of a healthful of communication in the school.